2021
DOI: 10.3389/fimmu.2021.716317
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antibiotics and Proton Pump Inhibitors on Efficacy and Tolerance of Anti-PD-1 Immune Checkpoint Inhibitors

Abstract: BackgroundThe use of antibiotics (ATB) and proton-pump inhibitors (PPI) alters the composition and diversity of the gut microbiota, which can influence the immune system, consequently interfering with response to anti-PD1 immune checkpoint inhibitors (ICI). We assessed the impact of ATB and/or PPI use on the efficacy and safety of ICI.MethodsTwo hundred twelve patients treated with anti-PD1 ICI for non-small cell lung carcinoma, melanoma, upper airway & digestive tract carcinoma or renal cell carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 38 publications
4
56
0
Order By: Relevance
“…Finally, 33 studies, of which 24 were peer-reviewed journal publications and 9 were conference abstracts, were included in the systematic review and meta-analysis. 12 , 13 , 19 49 The flow diagram of identifying the eligible studies is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 33 studies, of which 24 were peer-reviewed journal publications and 9 were conference abstracts, were included in the systematic review and meta-analysis. 12 , 13 , 19 49 The flow diagram of identifying the eligible studies is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…FMT from the obesity-associated human gut microbiota to mice can induce vascular dysfunction and glucose intolerance, and FMT from lean donors to patients with obesity can promote metabolic benefits (Mocanu et al, 2021;Russo et al, 2021). Recent studies over the past decade have revealed that many environmental factors, including diet, antibiotic exposure, energy intake and exercise, can dramatically influence the gut microbiota (Du et al, 2021;Giordan et al, 2021;Shi et al, 2021). Dietary fiber has been shown to improve obesity and is considered a potential therapy because it increases microbial fermentation of SCFAs (Schäfer et al, 2021;Thomson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Antacid agents such as proton pump inhibitors (PPIs) and histamine-2-receptor antagonists (H2RAs) are commonly prescribed for extended periods in NSCLC patients, and these drugs have been suggested to modify the activity of anticancer therapies through several mechanisms, including gut microbiome changes [20]. However, available literature reports controversial results, with some studies highlighting a trend towards lower ICI activity and worse clinical outcomes in patients receiving antacids and immunotherapy, and other trials reporting no effect or even longer survival in subjects treated with concomitant PPIs or H2RAs [21,22]. Based on these premises, we performed a systematic review and meta-analysis to investigate the impact of antacids on NSCLC patients treated with ICIs.…”
Section: Introductionmentioning
confidence: 99%